Advances in Usability and User Experience Proceedings of the AHFE 2017 International Conference on Usability and User Experience, July 17-21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA - Ahram, Tareq; Falcão, Christianne; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book focuses on emerging issues in usability, interface design, human computer interaction and user experience, with a special emphasis on the research aimed at understanding human-interaction and usability issues with products, services and systems for improved experience. It covers modeling as well as innovative design concepts, with a special emphasis to user-centered design, and design for special populations, particularly the elderly. Virtual reality, digital environments, heuristic evaluation and feedback of devices' interfaces (visual and haptic) are also among the topics covered in this book. Based on the AHFE 2017 Conference on Usability & User Experience, held on July 17-21, 2017, in Los Angeles, California, USA, the book describes new findings, research methods and user-centered evaluation approaches.
What does the eye want? An investigation of interface parameters to ensure intuitive gaze controlled interactions for multidimensional inputs -- Evolution of user experiences and interfaces for delivering context-aware recommendations to information analysts -- A smarTactile map designed for the visually impaired to improve spatial cognition -- Usability evaluation on learning management system -- Not ready for Industry 4.0: Usability of CAx systems -- User-centered design in the U.S. Air force additive manufacturing; case studies on tools, jigs, and topology optimization -- Understanding the international space station crew perspective following long duration missions through data analytics and visualization of crew feedback -- The relationship between the severity of usability problems and user skin conductance levels during human-computer interactions -- From healthcare to human-computer interaction: Using framework analysis within qualitative inquiry -- Ease of use and medical devices- perceptions and reality -- Comparison between color and grayscale interfaces: Recipe usability of a dietary plan in diabetics -- Preventing trauma accidents in children: An ecosystem based on interactive ludic activities for mobile and web-based environments -- Designing the remote aerodrome flight information service systems interface base on human centered design approach -- Smart blanket: A real-time user posture sensing approach for ergonomic designs -- An augmented reality application to enhance the children's engagement in an early development method for mathematics literacy -- Usability heuristic evaluation of scientific data analysis and visualization tools -- How screen magnification with and without word-wrapping affects the user experience of adults with low vision -- Research on multi-factor sofa inclination comfort based on user experience. .
Keywords: User interfaces (Computer systems).; Human-computer interaction; Engineering design; Human-machine systems; Computational intelligence; User Interfaces and Human Computer Interaction; Engineering Design; Interaction Design; Computational Intelligence